The Little Data Book on Financial Inclusion 2015 - World Bank (Springer, 2015)
"The Little Data Book on Financial Inclusion 2015 is a pocket edition of the Global Financial Inclusion (Global Findex) database published in 2015. This data set represents a second round of data collection, following the initial round three years earlier. The database provides nationally representative, demand-side data on access to and use of accounts, credit, payments and savings by adults age 15 and above in 143 economies. In addition, new indicators measure people's ability to manage risk. This book presents data for selected indicators by country, region, and income group. For some indicators the data are disaggregated by age, gender, income level, and rural residence."